4(3c-6)=2c+11

Simple and best practice solution for 4(3c-6)=2c+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3c-6)=2c+11 equation:


Simplifying
4(3c + -6) = 2c + 11

Reorder the terms:
4(-6 + 3c) = 2c + 11
(-6 * 4 + 3c * 4) = 2c + 11
(-24 + 12c) = 2c + 11

Reorder the terms:
-24 + 12c = 11 + 2c

Solving
-24 + 12c = 11 + 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
-24 + 12c + -2c = 11 + 2c + -2c

Combine like terms: 12c + -2c = 10c
-24 + 10c = 11 + 2c + -2c

Combine like terms: 2c + -2c = 0
-24 + 10c = 11 + 0
-24 + 10c = 11

Add '24' to each side of the equation.
-24 + 24 + 10c = 11 + 24

Combine like terms: -24 + 24 = 0
0 + 10c = 11 + 24
10c = 11 + 24

Combine like terms: 11 + 24 = 35
10c = 35

Divide each side by '10'.
c = 3.5

Simplifying
c = 3.5

See similar equations:

| (5/3)m=-70 | | 3c^2=5c | | 8x-7*3=11 | | 2a-4=12 | | 3(x+2)+2(x-1)=8x-4 | | 12x+24=5 | | 7x+16=5*(8-x) | | (3a-9)=2a-10(a-1) | | (5x-19)5/6=32 | | (-3/7)*(m+5)=3+2m | | p=24 | | 9n+68=7n+2(n-2) | | (6/7)x=-24 | | (-3/7)*(m-9)=3+6m | | 12a^2-13=35 | | 7x+12=13+7x | | B^2+20+36=0 | | 7x(-2x^4)= | | 2y=3y-3 | | 5x-2=x+14 | | x^2-7x=-6 | | 2x^2+28x-96=0 | | 2x^2+28x+96=0 | | 3x^2+14x+49=0 | | 5x^2-21x=0 | | 1x+27=63-2x | | X=-0.83-3 | | -3(-y-3)+3y=4 | | x^2+4= | | x^2-10x-4=10 | | 3x+9=7-1x | | 4(6z-1)-5(z+8)=9(2+1) |

Equations solver categories